Space-time correlation in inferring Islamic rulings - Hasan, Md. Mahmudul (2020)
In inferring rulings related to a particular spatiotemporal setting, classical Islamic jurists invariably emphasized a close correlation between the primary texts of Islam and local realities. Giving opinions or passing verdicts only based on the letter of the texts, without understanding the spirit and without considering circumstantial factors, can be detrimental and create controversies. This may even make a particular Islamic teaching irrelevant to society.